Dietary vitamin or mineral mix removal during the finisher period on broiler chicken performance - Maiorka, A.; Laurentiz, A. C.; Santin, E.; Araujo, L. F.; Macari, Marcos [UNESP] (Poultry Science Assoc Inc, 2002)
The effect of dietary vitamin (VS) and mineral (MS) mix withdrawal between 42 and 49 d of age on broiler chicken performance was evaluated. The diets were formulated based on corn and soybean meal, and the experiments were conducted in floor pens using wood shavings as litter. Trial I evaluated withdrawal of VS and MS mix at 42, 45, and 49 d. The results of this trial showed that VS and MS mix withdrawal at 42 d of age did not impair feed intake (FI) or weight gain (WG), but feed conversion (FC) was improved (P = 0.043) when both mixes were maintained in the diets until 49 d of age. Trial 2 assessed the withdrawal of VS or MS mix at 42 d of age. FI and WG were not affected by withdrawal, but FC was poorer (P = 0.035) for the broilers fed the diet without VS. The relative liver weight was reduced by VS or MS mix withdrawal (P = 0.014 and P = 0.001, respectively). Carcass, breast, and leg yields were not affected by VS or MS mix withdrawals in either trial. The findings of the study suggested that VS mix withdrawal during the final period of broiler chicken growth was more deleterious than the withdrawal of MS mix, because it affected FC ratio. VS or MS withdrawal during this period did not affect carcass yield.
Keywords: broiler; mineral; vitamin; withdrawal feed